1996
DOI: 10.1200/jco.1996.14.11.2950
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly intensified ambulatory chronomodulated chemotherapy with oxaliplatin, fluorouracil, and leucovorin in patients with metastatic colorectal cancer.

Abstract: This highly effective fully ambulatory outpatient regimen deserves further testing in randomized trials both in chemotherapy-naive patients and before surgery to remove metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 16 publications
5
37
0
1
Order By: Relevance
“…When OHP is infused in a chronomodulate setting (as a 12-h infusion) or flat infusion for 5 days, these hypersensitivity reactions do not occur. In particular, 151 patients submitted to 1087 constant rate continuous infusion courses of OHP, and 491 patients submitted to 3106 chronomodulate OHP courses did not experience any hypersensitivity reactions (Caussanel et al, 1990;Levi et al, 1992Levi et al, , 1993Levi et al, , 1994bLevi et al, , 1997Levi et al, , 1999Bertheault-Cvitkovic et al, 1996). Therefore, the incapacity of these schedules to produce hypersensitivity might be due to a long time infusion rather than to failure of activation of the immune system (which presents a circadian rhythm) in a chronomodulate setting (Levi et al, 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…When OHP is infused in a chronomodulate setting (as a 12-h infusion) or flat infusion for 5 days, these hypersensitivity reactions do not occur. In particular, 151 patients submitted to 1087 constant rate continuous infusion courses of OHP, and 491 patients submitted to 3106 chronomodulate OHP courses did not experience any hypersensitivity reactions (Caussanel et al, 1990;Levi et al, 1992Levi et al, , 1993Levi et al, , 1994bLevi et al, , 1997Levi et al, , 1999Bertheault-Cvitkovic et al, 1996). Therefore, the incapacity of these schedules to produce hypersensitivity might be due to a long time infusion rather than to failure of activation of the immune system (which presents a circadian rhythm) in a chronomodulate setting (Levi et al, 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…The platinum compound oxaliplatin is frequently used in the treatment of colorectal cancer patients that are resistant to 5FU, and can also be used in combination with 5FU or CPT-11, improving response rates and progression-free survival (Levi et al, 1993;Bertheault-Cvitkovic et al, 1996;Machover et al, 1996;de Gramont et al, 1997de Gramont et al, , 2000Andre et al, 1999;Maindrault-Goebel et al, 1999;Giacchetti et al, 2000). Oxaliplatin disrupts DNA replication and transcription by forming intrastrand DNA adducts, but the downstream molecular events underlying the cytotoxic effects of this chemotherapeutic agent have not been well characterised.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have demonstrated that 5- or 14-day schedules of chronomodulated 5-FU-based chemotherapy are less toxic, enable 5-FU dose intensity escalations by approximately 25% and significantly improve antitumor activity [20, 21, 22, 23]. To date, the three-drug chronotherapy regimen with 5-FU, LV and oxaliplatin used by Levi et al [23]is apparently one of the most active regimens in metastatic colorectal cancer with a response rate, validated in multicenter phase III randomized studies, over 50% [23, 30, 31]. In this three-drug regimen, on the basis of preclinical observations, 5-FU and LV were administered as a sinusoidally modulated infusion for 12 h between 10 p.m. and 10 a.m., with peak flow rates at 4 a.m. A similar infusion schedule was used by Bjarnason et al [22], but 5-FU+LV were infused over 14 days and only 62.5% of the total daily dose were administered over 7 h around the infusion peak which occurred at 3–4 a.m.…”
Section: Discussionmentioning
confidence: 99%